Hot Spots Analysis of Fishing Vessels in Anambas Islands 2014 - 2020 - Laia, Dominikus Yoeli Wilson (Jakarta Technical University of Fisheries, 2023)
The Anambas Islands is one of the regencies in the administrative area of the Riau Islands Province. The sea waters of the Anambas Islands are one of the regions that are strategic in Indonesia because they are located in the South China Sea and bordered by Malaysia, Singapore, Vietnam, and Thailand. Understanding the location of hot spots of fishing activities in this area is very useful for knowing fishing areas as the basis for fisheries management, and potential fish stocks and distributions estimation. This study aims to determine the distribution of fishing vessels in the Anambas Islands, and the distribution of hot spots of fishing vessel locations in the Anambas Islands from 2014 to 2020. The method used is Optimized Hot Spot Analysis which runs the Hot Spot Analysis algorithm by calculating Getis-Ord Gi* statistics on each pixel of the fishing vessels detection image. The study found that the Tokongnanas hot spots cluster was a cluster that consistently appeared from 2014 to 2020. The Mubur, SW Munjan, E Munjan, S Lingai, and Mengkait hot spot clusters were found relatively new. The increase in the number of fishing boats detected in those new hot spot clusters is thought due to the increasing number of squid fishing gear in the area.